Study of the Impact Irregular Concrete Facilities with the Shear Walls Based: The Effect of Soil-Structure Interaction with ABAQUS Software - Wisam Fawzi Aljuhaishi; Javad Esfandiari (Journal of Techniques)
In the present study, the effect of irregularity of structures of the concrete with special shear walls has been analyzed and modeled by considering the effect of soil-structure interaction by dynamic analysis method with ABAQUS software. The results are presented in the form of diagrams with different soil interaction conditions, the effect of the number of layers was investigated for different soils. The results showed that the bearing system of the flexural frame and the concrete shear wall under the lateral load of the earthquake have good strength and ductility, which makes this issue. This structural system should be used for cities with very high earthquake risk. As the number of floors increases, the effect of the shear walls on increasing the bearing capacity decreases. As the number of floors increases, the final displacement of the frame increases. The results showed that for soil type 1(hard soil which Vs=1000 m/s, v=0.15, q=50000 Kg/m2, P=2000 Kg/m3, r=0.5 m) structural system of concrete shear walls with better displacement, maximum structural stiffness, better behavior was observed in the structure. Three-story frame with concrete shear wall has a significant increase compared to similar frames with more floors, which shows the good performance of this system in structures with fewer floors.